The Effect of Empowering Leadership on Happiness at Work Using Job Crafting as a Mediation Variable on Bank Pengkreditan Rakyat (BPR) Profidana Paramitra Employess - Fajrunnikmah, Bonafida Isma; Probosari, Ninik (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study aims to determine and analyze the effect of Empowering Leadership on Happiness at Work Using Job Crafting as a Mediation Variable on Bank Pengkreditan Rakyat (BPR) Profidana Paramitra Employess in Bantul, DIY. This type of research is quantitative research. The population of this study were all permanent employees of 44 employees with saturated sampling (census), the majority aged 21 to 32 of 22 employees (50%), female sex of 27 employees (61.4%), had studied There are 40 employees (90.9%) with undergraduate degree, and 36 employees (81.8%) have worked for 1-11 years for 1-11 years. The data analysis method uses the Structural Equation Model (SEM) method with the help of SmartPLS 3.0 software. The results of this study state that there is a significant positive effect of empowering leadership on happiness at work. There is a significant positive effect of empowering leadership on job crafting. There is a significant positive effect of empowering leadership on happiness at work which is mediated by job crafting.